2017
DOI: 10.18203/2394-6040.ijcmph20171361
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of hypertension among the bank employees of Western Maharashtra – a cross sectional study

Abstract: INTRODUCTIONHypertension, the -silent killer‖ -is a modern day's epidemic and is an increasingly important medical and global public health issue due to its role in causation of coronary heart disease, stroke and other vascular complications.1 It is defined as systolic blood pressure measuring more than or equal to 140 mm of mercury and diastolic blood pressure measuring more than or equal to 90 mm of mercury recorded in an individual according to JNC 7.2 The global prevalence of raised blood pressure in adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 12 publications
5
15
2
Order By: Relevance
“…26 School teachers in Saudi Arabia 27 reported a hypertension prevalence of 25%. Consistent with prior findings, 13 , 28 our study had a higher prevalence of hypertension among older adults. Hypertension prevalence in the age group of 45–54 years (39.8%) reported from general population in India 29 was higher than the present study results of 25.6% hypertension prevalence in the same age group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…26 School teachers in Saudi Arabia 27 reported a hypertension prevalence of 25%. Consistent with prior findings, 13 , 28 our study had a higher prevalence of hypertension among older adults. Hypertension prevalence in the age group of 45–54 years (39.8%) reported from general population in India 29 was higher than the present study results of 25.6% hypertension prevalence in the same age group.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have reported a cause-effect relationship between job strain and high blood pressure. 11 , 12 A study among bank employees in Maharashtra state of India reported a hypertension prevalence of 42% 13 whereas another study in workers of ammunition factory in western part of India reported a hypertension prevalence of 43%. 14 A Chinese study among the working population reported 23% hypertension prevalence and 8.5% control rate of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with findings from other studies done on bank workers 9,12,[20][21][22][23] . However there are studies which fail to establish a significant association between gender and hypertension 24,25 .Prevalence of hypertension among males is higher than in females in general population of Nepal 16,17 which corroborates with our study finding. Significant association was found between physical activity and hypertension in this study and similar findings were reported by many other studies 9,12,13 .…”
Section: Discussionsupporting
confidence: 94%
“…Significant association was found between physical activity and hypertension in this study and similar findings were reported by many other studies 9,12,13 . However, some studies have shown no significant association between physical activity and hypertension 20,26 . Our findings revealed that hypertension is significantly higher among participants with known history of diabetes as had been reported by other studies 10,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation